PEMBIAYAAN PROPERTY INDENT (KPR SYARIAH) DITINJAU DARI MAQASHID SYARIAH DAN QAWAIDUL FIQHIYYAH - Meichio Lesmana; Ahmad Suminto; Siti Nurma Rosmitha (Journal of Islamic Economics and Philanthropy, 2021)
In meeting the need for housing, people with low incomes are very difficult to own a house in cash. The development product which was originally a conventional product, namely KPR, but in Islamic banking the system is used with profit sharing/margin so that it is without usury. The focus of this paper discusses how maqashid sharia and qawaidul fiqhiyyah review Sharia mortgages which are currently one of the prima donna products in Islamic banking. The author uses a normative juridical method, namely legal research using secondary data sources. Normative, because this study will examine secondary data starting from the review of maqashid sharia and qawaidul fiqhiyyah in the field of Islamic banking, especially in Sharia mortgages. Operationally, normative juridical research is carried out by means of library research. The results of this study are Islamic mortgages are allowed because they are part of carrying out the goals of sharia or maqashid sharia in the part of maintaining family and property, it is also assessed that home ownership is a daruriyah need of every human being so that with this Sharia mortgage it can provide benefits for Muslims in general also according to qawaidul fiqhiyyah contracts in Sharia mortgages are allowed by referring to several fiqh rules.